Design projects on automotive controls - developing an automation lab for senior projects - (:unkn) unknown (Institute of Electrical and Electronics Engineers (IEEE), 2004)
This article describes several automotive controls-related senior design projects. In this project, a team of two students built several masked Simulink blocks comprising elements of a mean value engine model (MVEM) and assembled these blocks into a blockset in the Simulink block library. The MVEM blockset was used to create a virtual engine for which an idle-speed controller was designed. An interesting aspect of this project is that neither student was from the controls option, having taken only a compulsory introductory course on system dynamics and control. Yet, their first task after creating the MVEM engine model was to design a speed controller. The overall learning and design phases proceeded quickly due to the use of the sisotool graphical user interface (GU) in Matlab's control system toolbox. The aim of this project was to create an HIL and human-in-the-loop driving simulator for testing vehicle dynamics control algorithms, examining the effect of a steer-by-wire actuator on vehicle dynamics control (VDC) performance, investigating driver-controller interaction, and eventually for driver modeling.